A dendritically amplified fluorescent signal probe on SiO2 microspheres for the ultrasensitive detection of mercury ions. Issue 7 (27th February 2020) - Li, Chunli; Zhang, Yuqi; Cai, Qianqian; Jie, Guifen; Li, Chunxiang
Abstract : A new kind of dendritically amplified fluorescent signal probe was controllably fabricated by terminal deoxynucleotidyl transferase-catalyzed incorporation of nucleotides combined with bio-barcode amplification for ultrasensitive detection of Hg 2+ . Abstract : In this work, a new kind of dendritically amplified fluorescent signal probe on SiO2 microspheres was controllably fabricated by the terminal deoxynucleotidyl transferase (TdT)-catalyzed incorporation of nucleotides combined with bio-barcode (BBC) amplification for the ultrasensitive detection of Hg 2+ . A thymine T–Hg 2+ –T hairpin structure was first formed and further initiated the strand displacement amplification (SDA) reaction, generating a mimic target (MT). MT hybridized with a capture probe 1 (C1) on SiO2 microspheres, and the 3′-hydroxyl (OH) termini of MT initiated TdT-based DNA extension, producing abundant poly-guanine sequences (G1). Then, G1 hybridized with a capture probe 2 (C2) with abundant cytosine (C) species to assemble multiple C2/reporter probe-AuNPs onto the SiO2 microspheres. The reporter DNA further initiated TdT-based extension with a poly-T sequence (T1) to link large numbers of signal probes, which generated a very high fluorescence signal for the ultrasensitive detection of target Hg 2+ . This TdT-based signal amplification method coupled with SDA exhibits extraordinary sensitivity for Hg 2+ assay with a limit down to 1.0 aM. The proposed highly sensitive fluorescence strategy holds great potential for detecting targets in environmental and biological fields.